Septal perforation repair technique with bipedicle flaps: 3 cases report - Decq Mota, Sofia (2017)
Introduction: The nasal septum perforation results from interruption of bilateral septal mucoperichondrium, with subsequent necrosis and destruction of the underlying cartilage. There are several possible causes, but it is most often iatrogenic (due to septoplasty). Although it is often assymptomatic, it can cause significant symptoms such as nasal obstruction, nasal crusting, bleeding and whistle. Its surgical repair, as an alternative to the septal button, requires a lot of experience and technique, with several methods described in the literature. In our department we use bridge flaps, preferably bilaterally, in order to ensure the closing of the perfuration.Material and Methods: We describe 3 cases operated in the service, using the same technique. First, a perforation with 3 mm of diameter caused by septoplasty; second, a perforation with 5 mm of diameter, caused after FESS for epistaxis control; the third, of unknown cause, with a perforation with 11 mm of diameter.Results: We achieved complete closure in the 2 patients with the smaller perforations. The third patient has a small residual perforation, at 4 months postoperatively. There was resolution of the symptoms in all patients.Conclusions: The septal perforation is responsible for important symptoms and its closure is a desirable option against the placing of a septal button. There are several techniques. In this study we describe the use of bipedicle flaps with good results.